Optimising long-term athletic development: An investigation of practitioners` knowledge, adherence, practices and challenges - Till, K.; Lloyd, R. S.; McCormack, S.; Williams, G.; Baker, J.; Eisenmann, J. C. (PLOS ONE, 2022)
Long-term athletic development practices have been recommended for the past two decades. However, limited research exists exploring the knowledge and skills required by practitioners to optimise long-term athletic development. Therefore, this study aimed to evaluate the knowledge, adherence, practices, and challenges of practitioners responsible for delivering long-term athletic development. A mixed methods survey was completed by 236 practitioners (e.g., sport coaches, physical education teachers) consisting of four parts; 1) demographics, 2) knowledge, 3) adherence, and 4) practices and challenges. Quantitative and qualitative data were analysed by Friedman`s analysis of variance and thematic analyses, respectively. Quantitative findings showed practitioners 1) recognised their responsibility for delivering long-term athletic development, 2) have a familiarity with existing developmental models, and 3) had high adherence, focused upon health and wellbeing, to delivering long-term athletic development. However, practices associated with growth and maturity, monitoring and assessment, and the systematic progression and individualisation of training had lower adherence. Qualitative analysis indicated that practitioner`s perceived definitions of athleticism and long-term athletic development were inconsistent, especially according to the psychological components (i.e., confidence). Practitioners` descriptions of their long-term athletic development practices identified two higher order themes; 1) goals, in which long-term athletic development "is for life" and the importance of "an individual centered journey" highlighted as sub-themes; and 2) realities of delivering long-term athletic development, whereby variety in programme delivery, monitoring development and practical challenges were noted as key priorities. Eight practical challenges were identified including governance and priorities, resources, education, early specialization, high training volumes, staff communication, parents and youth motivation. This mixed method survey highlighted a multitude of knowledge, adherence, practices and challenges towards long-term athletic development. These novel findings can help inform policy to optimise long-term athletic development and to support the complex problem of developing a healthier, fitter and more physically active youth population.